2014
DOI: 10.3945/jn.114.197095
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity Is Associated with Anemia in Adult Mexican Women of Reproductive Age

Abstract: HFI is associated with anemia among adult Mexican women. Programs that reduce HFI may also be effective at reducing the risk of anemia among Mexican women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 40 publications
8
38
1
7
Order By: Relevance
“…A recent study of French adults [3] has identified a significantly poorer overall diet quality among food insecure individuals, with a higher consumption of sweet foods and a lower consumption of fruits, vegetables and fish. A greater risk for iron deficiency anemia among women has been found [44,45]. Reduced intake of certain nutrients, in turn, has been linked to irritability, nervousness, depression, and dementia, among others problems [37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of French adults [3] has identified a significantly poorer overall diet quality among food insecure individuals, with a higher consumption of sweet foods and a lower consumption of fruits, vegetables and fish. A greater risk for iron deficiency anemia among women has been found [44,45]. Reduced intake of certain nutrients, in turn, has been linked to irritability, nervousness, depression, and dementia, among others problems [37].…”
Section: Discussionmentioning
confidence: 99%
“…The regular consumption of such diets can lead to the double burden of malnutrition, whereby women, may suffer from obesity coupled with micronutrient deficiencies. The ‘sacrifice theory’ is another proposed mechanism suggesting that mothers tend to adopt unfavorable coping strategies, including sacrificing their own dietary intake and nutritional health, for the sake of their children [19, 20, 87]. Moreover, to manage feeding their families on limited budgets, mothers may skip meals and consume diets of low diversity that are calorically-dense yet of low nutritional value, which may in turn increase their risk of weight gain [80].…”
Section: Discussionmentioning
confidence: 99%
“…Household food insecurity has been associated in Mexico with negative health outcomes such as anaemia, obesity, diabetes and hypertension Fischer et al 2014;Morales-Ruan Mdel et al 2014). However, information concerning the association of food insecurity with mental health is lacking.…”
Section: Introductionmentioning
confidence: 99%